Knowledge of firefighters with special paramedic training of the emergency management of avulsed teeth - Cardoso, Leandro de Carvalho; Poi, Wilson Roberto [UNESP]; Barioni, Sônia Regina Panzarini [UNESP]; Sonoda, Celso Koogi [UNESP]; Rodrigues, Thais da Silveira; Manfrin, Thais Mara (Wiley-Blackwell Publishing, Inc, 2009)
Immediate replantation into the socket is the ideal procedure in cases of accidental avulsion of permanent teeth. In Brazil, firefighters with special paramedic training are in charge of providing first-aid care to victims of road accidents and might have to deal with tooth avulsions. This study assessed the knowledge of firefighters regarding the emergency management of avulsed teeth. Information was collected from a questionnaire submitted to 110 volunteer firefighters in seven cities in the São Paulo State (Brazil). The results revealed that 70.9% of the respondents did not know what tooth avulsion was; 53.6% did not know what tooth replantation was or defined it incorrectly; 60% would not act properly in tooth avulsion cases; 20.9% did not consider replantation of the avulsed tooth into the socket as a treatment option; the ideal time interval for tooth replantation was unknown to 40% of the interviewees; 90% of the participants answered that they would not be able to perform tooth replantation. Among those who considered themselves unable to perform tooth replantation, 47.3% chose saline as the best storage medium for an avulsed tooth, 21.8% chose milk, 3.6% chose the patient's mouth and 20% reported not knowing where to store the tooth; 81.8% of the firefighters reported not to have ever received any specific directions on tooth replantation and 100% of them considered this knowledge a requirement for first-aid care to accident victims. In conclusion, the knowledge of the surveyed firefighters regarding emergency management after tooth avulsion was unsatisfactory in several aspects that are important for the success of replantation procedures. Firefighters with special paramedic training should be educated on how to proceed in cases of dentoalveolar traumas and tooth avulsions in order to improve treatment prognosis and increase the survival rate of replanted teeth.